The impact of decellularization methods on extracellular matrix derived hydrogels. - Ahearne, Mark (My University, 2019)
Tissue-derived decellularized biomaterials are ideal for tissue engineering applications as they mimic the biochemical composition of the native tissue. These materials can be used as hydrogels for cell encapsulation and delivery. The decellularization process can alter the composition of the extracellular matrix (ECM) and thus influence the hydrogels characteristics. The aim of this study was to examine the impact of decellularization protocols in ECM-derived hydrogels obtained from porcine corneas. Porcine corneas were isolated and decellularized with SDS, Triton X-100 or by freeze-thaw cycles. All decellularization methods decreased DNA significantly when measured by PicoGreen and visually assessed by the absence of cell nuclei. Collagen and other ECM components were highly retained, as quantified by hydroxyproline content and sGAG, by histological analysis and by SDS-PAGE. Hydrogels obtained by freeze-thaw decellularization were the most transparent. The method of decellularization impacted gelation kinetics assessed by turbidimetric analysis. All hydrogels showed a fibrillary and porous structure determined by cryoSEM. Human corneal stromal cells were embedded in the hydrogels to assess cytotoxicity. SDS decellularization rendered cytotoxic hydrogels, while the other decellularization methods produced highly cytocompatible hydrogels. Freeze-thaw decellularization produced hydrogels with the overall best properties.
PUBLISHED
Keywords: Tissue engineering; Hydrogels; Decellularization; ECM